The Implementation of Expectation-Confirmation Model (ECM) in Analyzing the Relationship Between Gamification and Continuance Use Intention in Online Travel Industry - Juliana Juliana; Imam Jayanto; Murwani Wulansari; Muhammad Hery Santoso; Tri Apriyono (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
Online Travel Agent or abbreviated as OTA is one form of technological development in the tourism industry. Competence in the OTA business is getting tougher, along with that each OTA provides different services. One of the trends to increase user loyalty is by implementing the concept of gamification into the system. This study aims to determine the gamification factors that have an influence on continuance use intention in OTA users. This research uses a quantitative approach with 300 respondents taken using purposive sampling. The data was analyzed using PLS-SEM with SmartPLS. The research model used is taken from the modified Expectation-Confirmation Model (ECM). The results of this study found that two out of twelve hypotheses were rejected. Based on the ten accepted hypotheses, it can be concluded that novelty, trendiness and intimacy of gamification have a positive influence on continuance use intention through hedonic value and utilitarian value variables.